Endotracheal tubes : (Springhouse Corpoation, 1991)
This video covers the following topics: how endotracheal tubes work, patient preparation and intubation, taping methods, assuring proper tube placement, mouth and nasal care, suctioning, how to measure cuff pressure, drug administration through an endotracheal tube, repositioning the tube, cuff inflation, cuff deflation, extubation.Target audience: Nursing : undergraduate ; General Health Sciences : general.